ANALISIS PENGARUH BOOK TAX DIFFERENCES, AKRUAL DAN ARUS KAS OPERASI TERHADAP PERSISTENSI LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia 2012-2014) - JaisSetiawan, 13.05.52.0232; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2017)
This study examines the effect of book-tax difference, accruals and operating cash flow to earnings persistence. This research was conducted at the Indonesian Stock Exchange by using analysis unit manufacturing companies that have gone public The sampling method using purposive sampling the study period of 2012through 2014. The relationship and influence between variables or described using multiple regression analysis using SPSS 23. The results showed that large positive book tax difference and large negative book tax difference does not affect the persistence of earnings. While accruals and operating cash flow positive effect on earnings persistence.Keywords: Large Positive Book Tax Difference, Large Negative Book Tax Difference, Accruals, Operating Cash Flow and Earnings Persistence